2021
DOI: 10.1186/s40729-021-00297-z
|View full text |Cite
|
Sign up to set email alerts
|

Full arch rehabilitation in patients with atrophic upper jaws with zygomatic implants: a systematic review

Abstract: Background The main objective of this systematic review was to present the outcomes of the treatment with zygomatic implants (ZIs) in the rehabilitations of atrophic upper jaw. Findings An electronic database search in PubMed, along with a manual search, taking into account language and study period, was performed by two observers; any type of clinical trial and series that included the use of ZIs was used. In the search strategy, the following sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…A recent systematic review including data of 4556 ZIs with a follow-up of 12 years found a cumulative survival rate of 95.21% [ 26 ]. Another review with a shorter average follow-up reported a success rate of 98.22% [ 10 ]. The data of our study referred to an average follow-up of 12 years and the survival rate of the placed implants was around 76% (51/67), being significantly lower compared with those published by the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review including data of 4556 ZIs with a follow-up of 12 years found a cumulative survival rate of 95.21% [ 26 ]. Another review with a shorter average follow-up reported a success rate of 98.22% [ 10 ]. The data of our study referred to an average follow-up of 12 years and the survival rate of the placed implants was around 76% (51/67), being significantly lower compared with those published by the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic prophylaxis was made in all cases with Amoxicillin 3 g per day for 10 days. All patients were recommended rinses with 0.2% chlorhexidine and the use of a thermoplastic elastomeric (TPE) bristle during the first two weeks after the implant placement [ 10 , 14 ]. A full thickness flap was raised and the central/posterior part of the zygomatic complex was exposed, avoiding interference with the orbit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 While more zygomatic implants are available, they are still a relatively new implant solution. Therefore, what data is available should be shared 35,36 with patients as to complications 37,38 and survival rates for this type of implant.…”
Section: Evidence-based Dental Practicementioning
confidence: 99%